Sponsoring Esports to Improve Brand Image - Freitas, Bruno Duarte Abreu; Contreras-Espinosa, Ruth Sofia; Correia, Pedro Álvaro Pereira (Scientific Annals of Economics and Business, 2020)
This research aimed to identify how esports sponsorships affect the sponsors’ brand image. An exploratory focus was adopted along with a convergent-parallel mixed method with equal status. Twenty-two experts in esports sponsorships were interviewed and 5,638 esports fans were surveyed. Quantitative data was processed on SPSS 25 and qualitative data on NVivo 10. The two data sets were analysed separately from one another, but the results were interpreted together and given the same level of importance. The results showed that all experts believe that sponsoring esports can positively affect the sponsors’ brand image and roughly one-third of fans perceive more positively a small number of brands as a result of them sponsoring esports. This image improvement is, however, dependent on multiple variables, including activation strategy, brand type, and target audience. The findings are relevant for academics and companies looking to better understand the brand image effects of sponsoring esports. JEL Codes - M31; M37